2018
DOI: 10.1007/s00266-018-1154-6
|View full text |Cite|
|
Sign up to set email alerts
|

Metrics of the Aesthetically Perfect Breast

Abstract: Breast surgery has long been viewed as an art more than a science. However, defining and objectively measuring the ideal breast morphology and aesthetic proportions are fundamental for surgical planning and to setting the goals of surgery as well as to evaluate surgical outcomes. Despite the fact that much has been written about aesthetic and reconstructive breast surgery, there is still no real consensus about what the attributes are of an ideal breast. Moreover, there are in fact no objective standard measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…The dissimilar position of the nipples is especially important since NAC-positioning is considered the most important landmark in breast augmentation and the biggest determinant of patient satisfaction [32]. Several aesthetic algorithms have been proposed to pinpoint the most aesthetically pleasing positioning of the nipple [3,21,22]. Most of these studies agree on the notion that the ideal position of the nipple is centered on the apex of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…The dissimilar position of the nipples is especially important since NAC-positioning is considered the most important landmark in breast augmentation and the biggest determinant of patient satisfaction [32]. Several aesthetic algorithms have been proposed to pinpoint the most aesthetically pleasing positioning of the nipple [3,21,22]. Most of these studies agree on the notion that the ideal position of the nipple is centered on the apex of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that this nonstandard measurement is crucial in quantifying the extent of the breast mound and IMF descent in patients with slide-down deformity and thus determining the amount of elevation that will be required to restore them to an appropriate position ( Figure 1 ). 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…Women's breasts vary along many dimensions, such as shape, symmetry, and firmness (Atiye & Chahine, 2018), but many contemporary beauty systems reportedly objectify women in terms of their breast size (Calogero & Thompson, 2010;Mazur, 1986;Seifert, 2005;Tantleff-Dunn, 2001). In particular, large breasts are commodified and fetishised in many forms of mainstream Western media (Einon, 2012;Gerald & Potvin, 2009;Ward, Merriwether, & Caruthers, 2006), particularly media that (re)produce stereotypical gender role discourse (Graff, Murnen, & Krause, 2013;Yockey, King, Vidourek, Burbage, & Merianos, 2019) and heteronormative expectations (Murnen, Poinsatte, Huntsman, Goldfarb, & Glaser, 2015;Rodriguez & Hernandez, 2019;Rogers & Liebler, 2017; for a counter-point, see Webb, Vinoski, Warren-Findlow, Burrell, & Putz, 2017).…”
Section: Breast Size and Dissatisfactionmentioning
confidence: 99%
“…The body is a highly symbolic and important site for the creation, negotiation, and perpetuation of social and power relations (Backett-Milburn & McKie, 2001;Jeffreys, 2005;Scheper-Hughes & Lock, 1987;Thompson, Heinberg, Altabe, & Tantleff-Dunn, 1999). In this view, macro-level cultural factors -such as patriarchal structures (Bartky, 1990;Jeffreys, 2005), masculine aesthetics (Dworkin, 1974), and beauty systems (Bordo, 1993;Turner, 1984) -tie women's moral, economic, and socio-political worth to their physical appearance and willingness to enact personal body projects.…”
Section: Introductionmentioning
confidence: 99%